Multimodal Regulation Orchestrates Normal and Complex Disease States in the Retina - A. M. Olivares (Nature Portfolio, 2017)
Abstract Regulation of biological processes occurs through complex, synergistic mechanisms. In this study, we discovered the synergistic orchestration of multiple mechanisms regulating the normal and diseased state (age related macular degeneration, AMD) in the retina. We uncovered gene networks with overlapping feedback loops that are modulated by nuclear hormone receptors (NHR), miRNAs, and epigenetic factors. We utilized a comprehensive filtering and pathway analysis strategy comparing miRNA and microarray data between three mouse models and human donor eyes (normal and AMD). The mouse models lack key NHRS (Nr2e3, RORA) or epigenetic (Ezh2) factors. Fifty-four total miRNAs were differentially expressed, potentially targeting over 150 genes in 18 major representative networks including angiogenesis, metabolism, and immunity. We identified sixty-eight genes and 5 miRNAS directly regulated by NR2E3 and/or RORA. After a comprehensive analysis, we discovered multimodal regulation by miRNA, NHRs, and epigenetic factors of three miRNAs (miR-466, miR1187, and miR-710) and two genes (Ell2 and Entpd1) that are also associated with AMD. These studies provide insight into the complex, dynamic modulation of gene networks as well as their impact on human disease, and provide novel data for the development of innovative and more effective therapeutics.